Screening of wild okra (Abelmoschus moschatus) germplasm for okra yellow vein mosaic disease resistance in India - KUMARI, POOJA; SINGH, S P; GANGOPADHYAY, K K; CHALAM, V C; DUBEY, S C; SRINIVASA, N (The Indian Journal of Agricultural Sciences, 2021)
Okra yellow vein mosaic disease (OYVMD) is a major viral disease of okra crop caused by Okra yellow vein mosaic virus (OYVMV). The disease is responsible for direct yield loss in terms of both quantity and quality of capsules (fruits). Initially, DNA-A of coat protein, intergenic region and partial rep protein sequences were determined using OY2395F/OY680R specific primer and the amplified 1.2 Kb band product showed presence of OYVMV. Two years field screening of wild okra accessions (Abelmoschus moschatus ssp. moschatus) carried out during kharif 2017 and 2019 against OYVMD in agro-ecological conditions of New Delhi. Among seventy six (76) wild okra accessions 10 accessions, viz. EC360586, EC360794, EC360830, EC360900, EC359730, EC359836, EC359870, EC360351, EC361171 and EC361111 exhibited resistant (R) response in kharif 2017. While in 2019, out of these 10 promising accessions, four accessions, viz. EC360794, EC360586, EC360830 and EC361171 further showed R response. Rest of the tested lines showed either moderately resistant (MR) or susceptible (S) response. Average percent disease incidence (PDI) value was 19.51% and range value was 4.46 to 64.06% for the first year of field screening. Whereas the recorded average PDI were 21.77% with the range value of 4.36 to 67.33% in the second year. For both the years, out of 76 accessions, four accessions, viz. EC360794, EC360586, EC360830 and EC361171 were found promising and exhibited R response consistently. These promising lines could be utilized in breeding programmes for development of varieties resistant to OYVMV.